2018
DOI: 10.1039/c8cp02853b
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio design of light absorption through silver atomic cluster decoration of TiO2

Abstract: A first-principles study of the stability and optical response of subnanometer silver clusters Agn (n ≤ 5) on a TiO2(110) surface is presented. First, the adequacy of the vdW-corrected DFT-D3 approach is assessed using the domain-based pair natural orbital correlation DLPNO-CCSD(T) calculations along with the Symmetry-Adapted Perturbation Theory [SAPT(DFT)] applied to a cluster model. Next, using the DFT-D3 treatment with a periodic slab model, we analyze the interaction energies of the atomic silver clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 77 publications
7
66
0
Order By: Relevance
“…Both structures are highly stable, with adsorption energies (À4.53 eV for the pyramidal-shaped geometry at the PBE-D3(BJ)/U level) being of the same order of magnitude as in previous studies. 20,21 Next, we used the wavefunctions calculated at the PBE-D3(BJ)/U level in a follow-up HSE06 calculation at the relaxed geometries. It was thus found that the Ag 5 cluster donates its unpaired electron to the TiO 2 surface and loses its magnetic moment in either pyramidal-and trapezoidal-shaped structures.…”
Section: Surface Polaron Formation At the Ag 5 /Tio 2 Interfacementioning
confidence: 99%
See 4 more Smart Citations
“…Both structures are highly stable, with adsorption energies (À4.53 eV for the pyramidal-shaped geometry at the PBE-D3(BJ)/U level) being of the same order of magnitude as in previous studies. 20,21 Next, we used the wavefunctions calculated at the PBE-D3(BJ)/U level in a follow-up HSE06 calculation at the relaxed geometries. It was thus found that the Ag 5 cluster donates its unpaired electron to the TiO 2 surface and loses its magnetic moment in either pyramidal-and trapezoidal-shaped structures.…”
Section: Surface Polaron Formation At the Ag 5 /Tio 2 Interfacementioning
confidence: 99%
“…AQCs made of a few silver atoms seem to display better chemical and physical properties. The stability of Ag n clusters (n # 5) on the rutile surface has also been theoretically analysed, 20 predicting an enhanced light absorbance intensity of the material upon their deposition, as well as the appearance of secondary broad peaks with positions depending on the size and shape of the supported clusters. In particular, intense peaks have been identied in the visible region of the spectrum for the specic case of the Ag 5 AQC.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations